Interrelationships of Interferon and Immunity During Viral Infections - Glasgow, Lowell A. (The Rockefeller University Press, 1970)
Interferon is one determinant of host resistance. The immune responses, cellular or humoral, are other components. Cell-mediated responses appear to be involved in host resistance to certain viral infections, particularly the herpesvirus group and vaccinia virus. It is suggested that immune and interferon responses may complement one another and contribute to host resistance. The relative importance of each component depends upon the virus-host interaction. Finally, evidence has been presented which suggests that production of interferon as a result of antigen-sensitized cell interaction may further link these two components of the host response.